Case Report: Effect of Ajwa Date Consumption on LDL Levels in Perimenopausal Women - Hamsah, M.; Irwan, Irwan; Mappaware, Nasrudin Andi; Zulfamidah, Zulfamidah; Royani, Ida; Bulango, Nursanti (Newinera Publisher, 2024)
During perimenopause, there can be a decrease in estrogen production, which indicates the end of a woman’s reproductive years. The production of the hormone estrogen that continues to decrease will cause hypercholesterolemia. Decrease in LDL cholesterol levels can be increased by giving antioxidant properties, which are rich in vitamin C and contain flavanoids and phenolics that function as antioxidants. The method used in this study is Literature Review with Design Narrative Review. The result from the literature it was found the effect of giving ajwa dates (Phoenix Dactylifera L) before and after administration showed a change, namely a decrease in LDL levels after giving ajwa dates. This is because ajwa dates contain flavanoids, phenolics, and plant sterols that function as antioxidant that can prevent the formation of lipid peroxidation. The conclusion based on the results of the literature review, it can be concluded that giving ajwa dates to perimenopause women decreased LDL levels where ajwa dates have antioxidant functions to prevent lipid peroxidation to reduce LDL. The suggestion from the study is necessary to conduct further research on the effect of consumption of ajwa dates on LDL levels in perimenopause women using experimental methods of pretest and posttest design.